2021
DOI: 10.3390/cancers13092282
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Criteria for Reflex Testing for BRAF Mutations in Cutaneous Melanoma Patients

Abstract: Targeted therapy has been developed through an in-depth understanding of molecular pathways involved in the pathogenesis of melanoma. Approximately ~50% of patients with melanoma have tumors that harbor a mutation of the BRAF oncogene. Certain clinical features have been identified in BRAF-mutated melanomas (primary lesions located on the trunk, diagnosed in patients <50, visibly pigmented tumors and, at times, with ulceration or specific dermatoscopic features). While BRAF mutation testing is recommended f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…19,29 Recently, Zhou et al proposed that mutation testing be considered in patients with high risk (>4 mm, or >2 mm with ulceration) stage II primary melanomas, to pre-empt management options on anticipated disease progression. 8 Furthermore, recent Phase 3 trials of adjuvant systemic therapy in stage II melanoma have shown positive results. 30,31 Therefore, the BRAF mutation status will be increasingly important in earlier stages of disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,29 Recently, Zhou et al proposed that mutation testing be considered in patients with high risk (>4 mm, or >2 mm with ulceration) stage II primary melanomas, to pre-empt management options on anticipated disease progression. 8 Furthermore, recent Phase 3 trials of adjuvant systemic therapy in stage II melanoma have shown positive results. 30,31 Therefore, the BRAF mutation status will be increasingly important in earlier stages of disease.…”
Section: Discussionmentioning
confidence: 99%
“…7 Access to BRAF targeted therapy (dabrafenib + trametinib, vemurafenib + cobimetinib or encorafenib + binimetinib) is currently only available through the Australian Pharmaceutical Benefits Scheme in patients with a known BRAF mutation. 1,8,9 BRAF mutations can be identified through a range of molecular techniques, with varying degrees of specificity, tissue requirements, turn-around time and financial cost. 10 When internally validated and performed with appropriate positive and negative controls, immunohistochemistry (IHC) using a highly specific antibody for BRAF V600E (which accounts for approximately 80% of BRAF V600 mutations in melanomas) when strong 3+ and diffuse staining is present is robust evidence of the presence of a BRAF mutation and is sufficient to commence targeted therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al 3 propose that reflex testing criteria implemented by clinicians and pathologists can streamline treatment initiation. Optimally, the BRAF mutation status of melanoma patients will be known upon arrival to their first medical oncology appointment.…”
mentioning
confidence: 99%
“…4 In this study, pathologists reflexively ordered biomarker tests (EGFR, ALK) upon pathological confirmation of NSCLC diagnosis. 4 This review article synthesizes evidence of reflex testing reducing time to treatment initiation in breast, colon, lung, and ovarian cancer 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation